2020
DOI: 10.22435/mpk.v30i2.3044
|View full text |Cite
|
Sign up to set email alerts
|

Aktivitas Antimalaria Daun Gempol (Nauclea orientalis (L.) L) terhadap Plasmodium falciparum

Abstract: The use of gempol (Nauclea orientalis (L.) L) stem as a malaria medicine has been empirically and scientifically proven. This condition encourages exploitation which can lead to scarcity of raw materials. Substitution of plant parts as raw material for medicine is one of the innovations that can be done for the sustainability of the plant species. Leaves are one part of the plant that is often used as a raw material for medicine. The selection of leaves as the main ingredient has many advantages over ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(39 reference statements)
0
6
0
1
Order By: Relevance
“…The results of processing data in table 1-1 showed that the higher the dose of H atra extract was inversely proportional to the level of parasitemia because the larger the dose of the extract had the greater ability to suppress parasite growth (17,22) . At a dose of 100 μg/ mL extract, it showed the highest suppression of parasitemia levels (0.29 %), the same as the G2 group that received chloroquine (with a dose of 100 μg/mL, it was able to suppress the parasite level until it was undetectable or 0%) (17,23) .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results of processing data in table 1-1 showed that the higher the dose of H atra extract was inversely proportional to the level of parasitemia because the larger the dose of the extract had the greater ability to suppress parasite growth (17,22) . At a dose of 100 μg/ mL extract, it showed the highest suppression of parasitemia levels (0.29 %), the same as the G2 group that received chloroquine (with a dose of 100 μg/mL, it was able to suppress the parasite level until it was undetectable or 0%) (17,23) .…”
Section: Discussionmentioning
confidence: 91%
“…Observations of the growth of parasites on negative controls showed the highest percentage. This is thought to occur due to the natural response of the P. falciparum parasite to defend itself in environmental conditions that are not suitable for its survival, so the parasite seeks to speed up the process of its growth (23,24) . The negative control group contained only media containing erythrocytes and P.falciparum strains of 3D7 without the administration of drugs or extract ingredients that could inhibit its growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that the optimal extract concentration was 26%, exhibiting antimalarial activity with an 8.6% reduction in parasitemia levels. 9 Various herbal plants have been studied to prove the effectiveness of alkaloid compounds as antimalarials, such as papaya leaf extract (Carica papaya), guava leaf extract (Psidium guajava), 17 merkubung leaf extract (Macaranga gigantea), 18 gempol leaf extract (Nauclea orientalis L.), 19 and noni fruit extract (Morinda citrifolia L.). 20 Based on the previous studies outlined above, it is evident that many herbal plants have the potential as antimalarials.…”
Section: Discussionmentioning
confidence: 99%
“…Plants of the genus Nauclea (Rubiaceae) are frequently used as folk medicines for the treatment of various diseases. Antimalarial activity of the hexane (IC 50 = 1.93 μg/mL) and methanol (IC 50 = 3.91 μg/ mL) fractions of Nauclea orientalis leaves against 3D7 P. falciparum was observed [ 63 ].…”
Section: Novel Antimalarials Derived From Plant Extracts and Isolated...mentioning
confidence: 99%